Training in Early Detection of Autism Spectrum Disorder for Early Childhood Educators and Achieving Mothers' Well-being - Henny Puji Astuti; Dewi Retno Suminar; Primatia Yogi Wulandari; Fitri Andriani; Cholichul Hadi; Nur Ainy Fardana (Jurnal Pemberdayaan Masyarakat, 2025)
The lack of ability of early childhood educators in the early detection of ASD can hinder learning objectives. On the other hand, lack of parental well-being also affects children's growth and development. This community service activity aims to help early childhood educators recognize and develop early detection skills for Autism Spectrum Disorder (ASD) in children, thereby promoting the well-being of mothers, so that they can provide appropriate treatment. The training method used is the in-on-in approach, which involves learning, application, and evaluation/reflection. At the learning stage, teachers participate in a workshop that includes lecture techniques, question-and-answer sessions, simulations, and mentoring. At the application stage, teachers and mothers conduct early detection of ASD in children. Teachers work on training and collect assignments. Then, at the evaluation/reflection stage, we use quantitative and qualitative descriptive analysis. The results of this activity show an increase in early childhood educators' knowledge and skills regarding the early detection of ASD in children and achieving mothers' well-being. Based on the pre-test and post-test results, there was a 28.85% increase in knowledge and skills related to the early detection of ASD. Meanwhile, mothers show better well-being in caring for children with ASD. This training has a long-term impact on achieving learning objectives and the well-being of mothers.